Dikotomi Moral dan Hukum sebagai Problem Epistemologis dalam Konstitusi Modern - Muhtamar, Syafruddin; Ashri, Muhammad (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2020)
This article discusses dichotomy between moral and legal consideration occuring in the modern constitutions that can be traced back in the thoughts of Thomas Aquinas and Niccolo Machiavelli.Â The analysis focuses on the epistemological aspects of this dichotomy that are rooted for long in the moral and legal concepts in the modern constitution.Through epistemological analysis, the authors conclude that the epistemic root of the dichotomy lie in the contrasting paradigm between supernatural law and modern positivism. While modern constitutionalism constructs moral concepts that presummes Divine truth, the legal concepts oriented to rational truth. These two concepts should be intergrated without dichotomy through the dictum 'moral exaltation in the primacy of the law' so that the law will be able to answer legal issues in the society.